2009
DOI: 10.1186/1757-1626-2-6999
|View full text |Cite
|
Sign up to set email alerts
|

Liver hydatid cyst perforated into the large bowel: a case report

Abstract: Perforation of the liver hydatid cyst into hollow abdominal organs is an extremely rare complication. A case of two synchronous hydatid cysts in an old lady is presented. The patient had one multilobular cyst perforated into the right colon and another one uncomplicated located at the right ovary. She underwent partial cystectomy, omentoplasty, right hemicolectomy, and total hysterectomy, and had an uneventful recovery.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
11
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 3 publications
(3 reference statements)
2
11
0
Order By: Relevance
“…A case reported by Bougioukas et al showed the right lobe of the liver's hydatid cyst with perforation into the right colon and an uncomplicated calcified right ovarian cyst, in addition to advanced age in this female patient, characteristics which were similar to our case [9]. In Restivo et al's study, a 64-year-old male patient, calcified cysts in segment 4 with a diameter of 6 cm as a result of migration with hepatic hydatid-colonic fistula associated with development of intestinal obstruction was reported [14].…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…A case reported by Bougioukas et al showed the right lobe of the liver's hydatid cyst with perforation into the right colon and an uncomplicated calcified right ovarian cyst, in addition to advanced age in this female patient, characteristics which were similar to our case [9]. In Restivo et al's study, a 64-year-old male patient, calcified cysts in segment 4 with a diameter of 6 cm as a result of migration with hepatic hydatid-colonic fistula associated with development of intestinal obstruction was reported [14].…”
Section: Discussionsupporting
confidence: 87%
“…Hollow abdominal organ perforation is very rare [5]. The duodenum, stomach and colon have also been reported on in connection with hydatid cysts [6][7][8][9]. Ultrasonography (US) and computed tomography (CT) are used as major methods of diagnosis.…”
Section: Introductionmentioning
confidence: 99%
“…Since our case was operated for the hydatid cyst in the liver, it was recognized that cysts in these two organs were primary cysts from the liver. The pre-operative diagnosis of cysts in our case was conducted with USG, MRI and CT consistent with the literature (3)(4)(5)(6)11,12) and the cuticular layer of the cyst was revealed with histopathological methods post-operationally.…”
Section: Discussionsupporting
confidence: 75%
“…The symptoms could differ based on the size and localization of the cysts (1)(2)(3)(4). Clinical history, serologic tests and various imaging techniques such as ultrasonography (USG), computed tomography (CT) and magnetic resonance imaging (MRI) can help make the diagnosis of cyst hydatid (3)(4)(5). The aim of the present study was to present a case with secondary hydatid cysts in both uterus and colon.…”
mentioning
confidence: 99%
“…5 However rupture of hydatid cyst into the colon is extremely rare and there have been only a few reports in the literature. [6][7][8][9] We report a case of a liver hydatid cyst communicating with the hepatic flexure of colon which was discovered on surgery.…”
Section: Introductionmentioning
confidence: 99%